(untitled) (Global Journal of Medical Research, 2020)
Postoperative nausea and vomiting (PONV) can be a very distressing side effect following general anaesthesia. Patients and health care professionals report the avoidance of PONV is of equal or sometimes even greater concern than avoidance of postoperative pain.1It can result in increased morbidity, delay in hospital discharge and unexpected hospital readmission, thereby increasing the total medical costs2. Moreover, PONV has been a major cause of decreased patient satisfaction3. There are several physiologic complications of nausea and vomiting that are of concern to the anaesthesiologist. Some of them being visceral wound dehiscence, electrolyte disorders, raised venous pressure leading to bleeding, rise in intraocular and intracranial tension and aspiration pneumonia especially in the sedated post-operative patient.